Implementasi Kebijakan Klasifikasi dan Perizinan Rumah Sakit Tipe C pada Bangunan Prasarana dan Peralatan di Rumah Sakit Syarif Hidayatullah - Alfitra Sari, Debi; Handayani, Nida (PUBLICNESS: Journal of Public Administration Studies, 2023)
In this study, there are still type C hospital classification and licensing standards that has not been met by Syarif Hidayatullah Hospital, so on this basis research was conducted. The purpose of this study was to analyze the implementation of the classification and licensing policies of type C hospitals on buildings, infrastructure, and equipment at Syarif Hidayatullah Hospital. To measure the success of policy implementation, the theory of George C. Edward III is used. The research method used in this study uses a qualitative approach with a descriptive type of research. Data collection techniques were carried out by means of interviews, observation, and documentation. The results of the research in communication indicators have been well socialized, but there are obstacles in the coordination carried out by policy implementers. Indicator Resources are still inadequate due to insufficient financial resources and infrastructure resources that do not meet the type C hospital classification standards. The disposition is good, several efforts have been carried out such as coordination meetings, making requests for suggestions, and collecting data on what must be completed. to meet classification standards on buildings, infrastructure, and equipment. The hospital bureaucratic structure and the owner still have unanswered obstacles regarding the work organization of the Syarif Hidayatullah Hospital which has not been incorporated into Syarif Hidayatullah State Islamic University.